Identification of Work Stress, and Training in Influencing Employee Performance at PT Semen Indonesia Based on Descriptive Statistical Review - Imanda Ratining Putri; Djoko Soelistya (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to identify work stress, training and employee performance at PT Semen Indonesia (Persero) Tbk Gresik in descriptive analysis. This research uses quantitative methods with a descriptive approach. The instrument used in this study was a questionnaire filled out by 142 employees. The questionnaire measured employees' perceptions of work stress and the training they received, as well as an evaluation of their performance. The results showed that the level of employee work stress was in the "Moderately" category with a mean value of 2.93, while the level of training was in the "agree" category with a mean value of 3.75. The employee performance is in the "agree" category with a mean value of 3.67. Descriptive analysis shows that the lowest indicator of work stress is work targets that are considered to exceed employee abilities, while the highest indicator of training is training material delivered in an interesting way. From these results it can be concluded that although there is a significant level of job stress, the training provided can help improve employee performance.